2020
DOI: 10.3233/jpd-202156
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Outreach Program and Practical Strategies for Patients with Parkinsonism in the COVID-19 Pandemic1

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has upended daily life and neurologic care for most patients, including those with Parkinson’s disease and parkinsonism. Disruptions to routine care, high volumes of patient and caregiver calls, and our patients’ risk of infection and complications inspired a proactive COVID-19 outreach program. This program targets patients with advanced Parkinson’s disease and related disorders, specifically those who are homebound, receiving or eligible for palliative care, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Teleconsultations also offer opportunities to provide proactive care, i.e., aiming to identify new medical issues early on so these can be managed timely, thereby preventing avoidable disability and reducing unnecessary costs. An illustrative example is a proactive outreach program that targeted homebound and vulnerable persons with advanced PD and related disorders [ 25 ▪ ]. A nurse or social worker proactively called these patients to discuss topics such as home safety, physical and mental wellbeing, medical care provisions, and also lockdown restrictions or scheduling of healthcare appointments.…”
Section: Teleconsultationmentioning
confidence: 99%
See 1 more Smart Citation
“…Teleconsultations also offer opportunities to provide proactive care, i.e., aiming to identify new medical issues early on so these can be managed timely, thereby preventing avoidable disability and reducing unnecessary costs. An illustrative example is a proactive outreach program that targeted homebound and vulnerable persons with advanced PD and related disorders [ 25 ▪ ]. A nurse or social worker proactively called these patients to discuss topics such as home safety, physical and mental wellbeing, medical care provisions, and also lockdown restrictions or scheduling of healthcare appointments.…”
Section: Teleconsultationmentioning
confidence: 99%
“…A nurse or social worker proactively called these patients to discuss topics such as home safety, physical and mental wellbeing, medical care provisions, and also lockdown restrictions or scheduling of healthcare appointments. Patients and caregivers reported that the program made them feel safe and supported [ 25 ▪ ]. Whether this proactive approach actually avoids medical deterioration and prevents e.g.…”
Section: Teleconsultationmentioning
confidence: 99%
“… Rhodes et al (2020) [ 84 ] Study is a recommendation (out of study design). Sennott et al (2020) [ 85 ] Study is a commentary (out of study design). Speretta and Leite (2020) [ 86 ] Study is an editorial (out of study design).…”
Section: Table A1mentioning
confidence: 99%
“…However, the aforementioned neuropathological data from autopsy studies call this hypothesis into question [8,9]. Regardless of such hypothesized protective effects, PD patients are nevertheless more vulnerable to complications following respiratory infections, and odds for their hospitalization or development of other comorbidities are higher than the general population [60]. Furthermore, parkinsonian symptoms after viral respiratory infections may hint us toward the less-known sides of the disease etiology and pathogenesis [61].…”
Section: Chorea Associated With Covid-19mentioning
confidence: 99%